PERANAN HUMAS PEMERINTAH KOTA SURABAYA DALAM PENGELOLAAN MEDIA RELATIONS SEBAGAI SARANA KOMUNIKASI KEPADA PUBLIK - Fatimah, Siti; Sumarah, Noorshanti; hamim, hamim (representamen, 2018)
This research is motivated by the role of public relations in the Surabaya City Governmentmedia relations activities as a means of communication with the public. Part of Surabaya citygovernment public relations in the field of information has a duty as a bridge of communication andinformation between the Government of the city of Surabaya with the community. This study aims todescribe the communication activities conducted by the Government public relations city of Surabayain superior Service and information embodies quality, improve information channels and aspiration.The theory is the theory of communication and public information Model theory Harold Lasswell.Research methods used in this research was qualitative research with type a descriptive. Thetechnique of collecting data through observation, in-depth interviews and documentation. Researchresults find communication activity conducted in Surabaya city government public relation Activitiesthe management of Media Relations as a means of communication to the public using a one-waycommunication, where is Surabaya city government public relations role as journalists indisseminating information to the public, and controls the news or information to mass media.In application of Surabaya City Government Public Relations are already maximizing the duties andfunctions of Public Relations Surabaya City Government in achieving and maintaining excellentservice and quality information, and to improve information channels and public aspirations, andmaintain harmonious relations with the media and the public.